Pemanfaatan Figma dalam Perancangan User Interface E-Commerce - Hita Hita; Djoni Djoni; Culita Culita; Roni Yunis (Pusat Riset dan Inovasi Nasional, 2024)
The user interface is an important element in an application or website. The choice of font type, color and layout in the user interface can be attractive and make it easier for users to explore applications or websites. The aim of this service is to provide training for participants consisting of 12th grade high school students to know and understand the basics of designing e-commerce user interfaces. The application used in user interface design training is Figma. The methods of this training service are introduction, understanding, teaching, testing and evaluation. The results of the evaluation show that the participants can design e-commerce user interfaces well and attractively. Of the total participants, 90% of participants had scores above 70 and only 2 participants scored 65 and 61. So it can be concluded that the use of Figma in designing e-commerce user interfaces increases the knowledge and understanding of the training participants.